(3EYQGH eTcd CMGOjK eSfO GHf GdLhRis
(3ChdgG (B:s
(3GdMeO ddg Ydi CaVGdg CeG HYO aEf LeGYI ef WdHI GdMOjK GdJeShG efi Cf Cedi Ydjge eNJUQkG ai EYQGH eG jTcd ef GdCdaGX GdhGbYI ai GdCMGOjK GdTQjaI s
(3BNQgG (B:s
(3hbhdgG (B: (3Edi GdUHM Ci fRd Edi UdGI GdUHM Ci djUdi UdGI GdUHM hgPG BNQ eG JjSQ LeYg ef EYQGH eTcd CMGOjK eSfO GdGeGe YHO GdQMef Hf GdLhRi hddg GdMeO hGdefI Ydi Pdc s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(961(3b(B) s
Keywords: (3GdfMhs